Nanoparticle-mediated functional and molecular photoacoustic imaging for assessment of metastatic lymph nodes - Dumani Jarquín, Diego Sayed (2018)
UCR::Rectoría::Oficina de Asuntos Internacionales y Cooperación Externa (OAICE)